Impact of Microbial Consortia on Microbial Population and Available Nutrients in Soil under Soybean Crop - N.G. Mitra and B.S. Dwivedi, Bablu Yaduwanshi, R.K. Sahu* (Journal of the Indian Society of Soil Science, 2021)
The present investigation was conducted to see the effect of microbial consortia on microbial population, available nutrients in soil and yield of soybean grown during 2018-19 under an ongoing All India Network Project on Soil Biodiversity and Biofertilizers at the Research Farm of Department of Soil Science and Agricultural Chemistry, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur, Madhya Pradesh, India. Coinoculation in the form of a consortium with Pseudomonas fluorescens (PGPR) Actinomycetes (Actino) and Arthrobacter (Arthro) was found beneficial in enhancing yield of soybean. Application of recommended dose of fertilizers (RDF) along with microbial consortium (PGPR+Actino+Arthro) recorded significantly higher amounts of available nitrogen (N), phosphorus (P) and potassium (K) which resulted in 43, 30 and 37 per cent, respectively over that of fertilized uninoculated control. Similarly, plots receiving RDF+PGPR+Actino+Arthro recorded significantly higher populations of Actinomycetes, Arthrobacter and PGPR at 25, 45 and 65 days after sowing which were 1.71, 1.42 and 1.52 log fold; 1.32, 1.28 and 1.31 log fold; and 1.56, 1.35 and 1.44 log fold, respectively over that of fertilized uninoculated control. In almost all cases, the treatment combinations of RDF+PGPR+Arthro, RDF+PGPR+Actino and RDF+Arthro+Actino exhibited similar performances. Seed and stover yields of soybean increased by 44 and 61 per cent, respectively over that of fertilized uninoculated control. It may be concluded that application of microbial consortia may be followed for enhancing soybean yield, available soil nutrients and microbial populations by direct as well as indirect beneficial effect.